Upaya Guru Dalam Meningkatkan Minat Belajar Tahsinul Quran Pada Siswa Sekolah Dasar - Adinda Putri Aulia; Khairuddin Lubis (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study examines strategies used by teachers to increase students’ interest in Tahsinul Qur'an learning at SD Nurul Qomar Percut. The study was motivated by the importance of developing children’s ability to read the Qur’an correctly and fluently from an early age, while students’ interest in Tahsinul Qur'an learning remains varied. A descriptive qualitative approach was employed, with data collected through classroom observations, in-depth interviews, and documentation. The participants were a Tahsinul Qur'an teacher and third-grade students. The findings indicate that students showed different levels of enthusiasm and participation. Some students were highly motivated, actively involved, and attentive, while others were less motivated, easily distracted, and quickly bored. The main obstacles to increasing students’ interest included low self-motivation, unsupportive social environments, and limited variation in teaching methods. To overcome these challenges, the teacher implemented several strategies, including creating an enjoyable and interactive learning atmosphere, applying engaging and communicative teaching methods, providing continuous motivation, habituating students to read the Qur’an before lessons, and giving individualized attention according to students’ characteristics and needs. The study concludes that teachers play a crucial role in fostering students’ interest in Tahsinul Qur'an learning. Creative, innovative, and student-centered teaching strategies can enhance students’ enthusiasm, participation, and engagement in learning to read the Qur’an.